Analyzing the Effects of Workload, Work Flexibility, Income Security, and Technological Support on Gig Workers’ Productivity in the Digital Economy - Putri Ayu Permata Devi; Titis Sri Wulan; Arif Subhan; Yuliati (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study examines the effects of workload, time flexibility, income security, and technological support on employee productivity in the gig economy. The research employs a quantitative approach using survey data collected from gig workers across the JABODETABEK region. Multiple linear regression analysis was applied to evaluate the partial and simultaneous relationships among the variables. The results show that all four independent variables significantly influence productivity. Workload positively affects productivity when maintained at an optimal level, while time flexibility provides the strongest individual effect by improving motivation and work–life balance. Income security also contributes significantly to productivity by ensuring financial stability and reducing stress related to income uncertainty. Among the variables, technological support exhibits the most dominant effect, enhancing efficiency and enabling smoother digital collaboration. The simultaneous test results further confirm that the interaction of workload, flexibility, income stability, and technological support produces a substantial and statistically significant influence on productivity. The findings of this study suggest that sustainable productivity among gig workers is determined by the synergistic balance of workload management, flexible scheduling, income stability, and technological integration within digital work environments. Keywords: Gig Economy, Income Security, Productivity, Technological Support, Time Flexibility, Workload